East Africa: Ethiopia - Agriculture, food security and climate change outlook - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Agriculture is the mainstay of Ethiopia’s economy and the primary source of employment for its population. It contributes 44% to the GDP and employs more than three quarters of the economically active population. The livestock sector contributes 16-20% to the national GDP and represents a key subsistence source for some 10 million pastoralists. Roughly 90% of total earnings come from agriculture. Agricultural systems are almost exclusively rain-fed. Of an irrigation potential of approximately 2.7 million hectares of land, only 2-3% of the cropland is currently irrigated. Initiatives that sustainably increase productivity, enhance resilience, and reduce/remove greenhouse gases (GHGs), are required, as well as planning to address trade-offs and synergies between these three pillars: productivity, adaptation, and mitigation.